Heavy Metal Detection in Soils by Laser Induced Breakdown Spectroscopy Using Hemispherical Spatial Confinement. (August 2015) - Meng, Deshuo; Zhao, Nanjing; Ma, Mingjun; Wang, Yin; Hu, Li; Yu, Yang; Fang, Li; Liu, Wenqing
Abstract Spatial confinement has great potential for Laser Induced Breakdown Spectroscopy (LIBS) instruments after it has been proven that it has the ability to enhance the LIBS signal strength and repeatability. In order to achieve in-situ measurement of heavy metals in farmland soils by LIBS, a hemispherical spatial confinement device is designed and used to collect plasma spectra, in which the optical fibers directly collect the breakdown spectroscopy of the soil samples. This device could effectively increase the stability of the spectrum intensity of soil. It also has other advantages, such as ease of installation, and its small and compact size. The relationship between the spectrum intensity and the laser pulse energy is studied for this device. It is found that the breakdown threshold is 160 cm−2, and when the laser fluence increases to 250 J/cm2, the spectrum intensity reaches its maximum. Four different kinds of laser pulse energy were set up and in each case the limits of detection of Cd, Cu, Ni, Pb and Zn were calculated. The results show that when the laser pulse fluence was 2.12 GW/cm2, we obtained the smallest limits of detection of these heavy metals, which are all under 10 mg/kg. This device can satisfy the needs of heavy metal in-situ detection, and in the next step it will be integrated into a portable LIBS instrument.